Difference between revisions of "Math 22 Partial Derivatives"
Jump to navigation
Jump to search
(→Note) |
|||
(12 intermediate revisions by the same user not shown) | |||
Line 5: | Line 5: | ||
<math>\frac{\partial z}{\partial y}=\lim_{\Delta y\to 0}\frac{f(x,y+\Delta y)-f(x,y)}{\Delta y}</math> | <math>\frac{\partial z}{\partial y}=\lim_{\Delta y\to 0}\frac{f(x,y+\Delta y)-f(x,y)}{\Delta y}</math> | ||
+ | |||
+ | We can denote <math>\frac{\partial z}{\partial x}</math> as <math>f_x(x,y)</math> and <math>\frac{\partial z}{\partial y}</math> as <math>f_y(x,y)</math> | ||
+ | '''Example:''' Find <math>\frac{\partial z}{\partial x}</math> and <math>\frac{\partial z}{\partial y}</math> of: | ||
+ | |||
+ | '''1)''' <math>z=f(x,y)=2x^2-4xy</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>\frac{\partial z}{\partial x}=4x^2-4y</math> | ||
+ | |- | ||
+ | |<math>\frac{\partial z}{\partial y}=-4x</math> | ||
+ | |} | ||
+ | |||
+ | '''2)''' <math>z=f(x,y)=x^2y^3</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>\frac{\partial z}{\partial x}=2xy^3</math> | ||
+ | |- | ||
+ | |<math>\frac{\partial z}{\partial y}=3x^2y^2</math> | ||
+ | |} | ||
+ | |||
+ | '''3)''' <math>z=f(x,y)=x^2e^{x^2y}</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>\frac{\partial z}{\partial x}=2xe^{x^2y}+x^2e^{x^2y}2xy</math> (product rule +chain rule) | ||
+ | |- | ||
+ | |<math>\frac{\partial z}{\partial y}=x^2e^{x^2y}(x^2)=x^4e^{x^2y}</math> | ||
+ | |} | ||
+ | |||
+ | ==Higher-Order Partial Derivatives== | ||
+ | 1. <math>\frac{\partial}{\partial x}(\frac{\partial f}{\partial x})=\frac{\partial^2 f}{\partial x^2}=f_{xx}</math> | ||
+ | |||
+ | 2. <math>\frac{\partial}{\partial y}(\frac{\partial f}{\partial y})=\frac{\partial^2 f}{\partial y^2}=f_{yy}</math> | ||
+ | |||
+ | 3. <math>\frac{\partial}{\partial y}(\frac{\partial f}{\partial x})=\frac{\partial^2 f}{\partial y\partial x}=f_{xy}</math> | ||
+ | |||
+ | 4. <math>\frac{\partial}{\partial x}(\frac{\partial f}{\partial y})=\frac{\partial^2 f}{\partial x\partial y}=f_{yx}</math> | ||
+ | |||
+ | '''1)''' Find <math>f_{xy}</math>, given that <math>f(x,y)=2x^2-4xy</math>, | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>f_x=4x-4y</math> | ||
+ | |- | ||
+ | |Then, <math>f_{xy}=-4</math> | ||
+ | |} | ||
+ | |||
+ | '''2)''' Find <math>f_{yx}</math>, given that <math>z=f(x,y)=3xy^2-2y+5x^2y^2</math>, | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>f_y=6xy-2+10x^2y</math> | ||
+ | |- | ||
+ | |Then, <math>f_{yx}=6y+20xy</math> | ||
+ | |} | ||
− | |||
Latest revision as of 16:21, 3 September 2020
Partial Derivatives of a Function of Two Variables
If , then the first partial derivatives of with respect to and are the functions and , defined as shown. We can denote as and as
Example: Find and of:
1)
Solution: |
---|
2)
Solution: |
---|
3)
Solution: |
---|
(product rule +chain rule) |
Higher-Order Partial Derivatives
1.
2.
3.
4.
1) Find , given that ,
Solution: |
---|
Then, |
2) Find , given that ,
Solution: |
---|
Then, |
This page were made by Tri Phan